Diagnostic Challenges of Pediatric Tuberculosis in a Severely Malnourished Child from a Rural Area: A Case Report - Clara Firhan; Dzaki Alfahri, Farhan (Rifa'Institute, 2026)
Introduction: Tuberculosis (TB) remains a major global health problem affecting both adults and children, particularly in TB-endemic countries. Children are vulnerable to TB infection, especially those with malnutrition, which significantly impairs immune function and increases disease severity, mortality, and diagnostic challenges. Malnutrition may obscure typical clinical manifestations and reduce the sensitivity of standard diagnostic tests, leading to delayed diagnosis and treatment. Case description: a four-year-old girl with severe wasting, multiple cervical lymphadenopathy, hypoalbuminemia, and severe dehydration. The patient had a history of incomplete immunization and close contact with a TB case. Initial investigations revealed a negative tuberculin skin test and chest radiography suggestive of bilateral bronchopneumonia. Despite intravenous ceftriaxone and supportive therapy, no clinical improvement was observed. Further evaluation using a rapid molecular test from a gastric aspirate confirmed TB. Discussion: Severe malnutrition likely contributed to immune anergy, resulting in false-negative initial diagnostic findings and delayed TB diagnosis. This case highlights the limitations of conventional diagnostic methods in malnourished children and underscores the importance of molecular testing in high-risk pediatric patients. Conclusion: TB and malnutrition have a bidirectional relationship that worsens clinical outcomes. Early TB screening in malnourished children and routine nutritional assessment in TB patients are essential to improve diagnosis, treatment outcomes, and survival.